Deskripsi Jenis Kesalahan dalam Menyelesaikan TIMSS-Based Test Ditinjau dari Kemampuan Awal pada Siswa SMP - Alimuddin; Ilham; Jubaedah (Program of Mathematics Education Department of Mathematics Faculty of Mathematics and Natural Sciences (FMIPA) Universitas Negeri Makassar (UNM), 2020)
This study aims to know the types of errors committed by students with high initial mathematical abilities and low initial mathematical abilities in solving TIMSS-based geometric questions for the cognitive domain of applying and reasoning. The type of this research is qualitative research using a descriptive approach. The research subjects as many as 2 people with of 1 people with early mathematical abilities and 1 people with low initial mathematical abilities from class VIII SMP. The research instrument consists of a TIMSS-based mathematical test devoted to the geometry content of the cognitive domain application and reasoning and interview guidelines. The difficulties analyzed were categorized using the Newman error category. The results of this research showed that: (1) For thecategory of applying , students with high initial mathematical abilities did not have errors, while students with low mathematical abilities had types of transformation errors, process skills, and encoding. (2) For the category of reasoning, the errors type of the students with high initial mathematical abilities are transformation, process skills, and encoding while students with low mathematical abilities had comprehension, transformation, process skills, and encoding errors.